(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tkachuk S. Features of technological education future teacher employment training In this article the problem of the formation and characteristics of technological culture of future teachers in preparing them in high school. We analyze the practical component of technological culture of the future teacher employment training.